Pulmonary hemorrhage in children with Alagille syndrome undergoing cardiac catheterization. Issue 2 (4th October 2019) - Adamson, Gregory T.; Peng, Lynn F.; Feinstein, Jeffrey A.; Yarlagadda, Vamsi V.; Lin, Amy; Wise‐Faberowski, Lisa; McElhinney, Doff B.
Abstract: Objectives: To evaluate the incidence, severity, and outcomes of pulmonary hemorrhage in children with Alagille syndrome (AGS) undergoing cardiac catheterization, and to find variables associated with hemorrhage in this population. Background: Children with AGS have a high incidence of bleeding complications during invasive procedures. It has been our impression that catheterization‐associated pulmonary hemorrhage is more common in children with AGS, but there are no published data on this topic. Methods: This was a retrospective single institution study of children with AGS undergoing catheterization from 2010 to 2018. Pulmonary hemorrhage was defined as angiographic or fluoroscopic evidence of extravasated blood in the lung parenchyma, or blood suctioned from the endotracheal tube with documentation of pulmonary hemorrhage by the anesthesiologist or intensivist. Univariate comparisons were made between catheterizations that did and did not have pulmonary hemorrhage. Results: Thirty children with AGS underwent 87 catheterizations, 32 (37%) with interventions on the branch pulmonary arteries (PA). There were 26 (30%) procedures with hemorrhage, the majority (65%) of which were self‐limited or required less than 24 hr of mechanical ventilation. Moderate and severe hemorrhage occurred only in children with tetralogy of Fallot (TOF; 5 of 14, 36%). A higher right ventricle to aorta systolic pressure ratio (1.0 [0.85–1.1] vs. 0.88 [0.59–1.0], p = .029) and interventions on the branch PAs (14 of 26, 54% vs. 18 of 61, 30%, p = .032) were associated with hemorrhage. Conclusions: Pulmonary hemorrhage was common in children with AGS undergoing both intervention and diagnostic cardiac catheterization, and was associated with TOF, higher RV to aorta pressure ratio, and interventions on the branch PAs.